2020
DOI: 10.3928/23258160-20200108-04
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis of Teleophthalmology Screening for Diabetic Retinopathy Using Teleophthalmology Billing Codes

Abstract: BACKGROUND AND OBJECTIVE: To evaluate the financial sustainability of teleophthalmology screening for diabetic retinopathy (DR) using telehealth billing codes. PATIENTS AND METHODS: The authors performed an Institutional Review Board-approved retrospective review of medical records, billing data, and quality metrics at the University of California Davis Health System from patients screened for DR through an internal medicine-based telemedicine program u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Our study showed a major decline in proportion of claims paid for remote retinal imaging over the decade, especially for CPT 92227 which decreased from 86.5% in 2011 to 51.9% in 2020, similar to findings from our tele-retinal screening program in California that used the same billing code. 6 Yet, this decline is occurring at a time of rapid expansion in using remote imaging to screen diabetics without eye diseases. In fact, claims for these patients were more often denied compared to those with eye diseases, even for 92227 which is designated for screening patients without retinopathy.…”
mentioning
confidence: 99%
“…Our study showed a major decline in proportion of claims paid for remote retinal imaging over the decade, especially for CPT 92227 which decreased from 86.5% in 2011 to 51.9% in 2020, similar to findings from our tele-retinal screening program in California that used the same billing code. 6 Yet, this decline is occurring at a time of rapid expansion in using remote imaging to screen diabetics without eye diseases. In fact, claims for these patients were more often denied compared to those with eye diseases, even for 92227 which is designated for screening patients without retinopathy.…”
mentioning
confidence: 99%
“…Another difference is that the ICER in our study is lower than the one in Hutton's. One reason could be that our low ICER may be due to the lower medical costs of South Korea than those found in the US [23][24][25][26]. Hutton indicated that if the price of ranibizumab (which has the greatest effect on ICER) fell from $1,916 to $900, ranibizumab would become more cost-saving than the combined treatment of PRP and ranibizumab in patients with DME.…”
Section: Discussionmentioning
confidence: 99%
“…However, the expansion of teleophthalmology programs has been hindered by inconsistencies in insurance coverage and reimbursements. At a large integrated health system in Northern California, Ellis et al found that 55% of charges for remote DR screening using telehealth codes were denied by non-capitated insurance plans, and 40% were denied by private insurers [ 14 ]. Despite the rapid increase in teleophthalmology utilization across the U.S., insurance coverage has declined according to national insurance claims data, with disproportionate impact on vulnerable populations such as older, Black, and lower-income patients [ 15 ].…”
Section: Introductionmentioning
confidence: 99%